Praktik Pembiayaan Bank Islam - M. Aditya Ananda (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2017)
Financing is financing provided by one party to another to support the planned investment, either by themselves or institution. Financing the Islamic bank can use a sale and purchase agreement such as murabaha, istishna, and greetings. Akad such as mudaraba, musharaka, ijara, qardul Hasan and others. Financing pattern of the first kind, can be calculated revenues are fixed for using the purchase contract. The calculation method using a flat profit margin, profit margins annuity method, the method of the average profit margins and declining profit margin method.